Quantitative Evaluation for the Threat Degree of a Thermal Reservoir to Deep Coal Mining - Yun Chen; Xinyi Wang; Yanqi Zhao; Haolin Shi; Xiaoman Liu; Zhigang Niu (Geofluids)
Taking the Suiqi coalfield located in North China as the object, where the coal seam burial depth is more than 1100 m, the water abundance of the roof pore thermal storage aquifer is better than average, the ground temperature is abnormally high, and hydrogeological data are relatively lacking, this paper selects and determines eight index factors that influence the mining of the coalfield. Based on the analytic hierarchy process (AHP), the index factor weight is defined, and then, the threat degree of the roof thermal storage aquifer to the coal mining is quantitatively evaluated and divided by using the fuzzy variable set theory. The evaluation results show that the threat degree of the roof in the eastern region is generally greater than that in the western region and that the closer it is to the coal seam outcrop line, the higher the threat degree is; near the boreholes, in the areas Qs1,Qs5, Qs8, Sx1, Tk5, Zc4, and Zc7, which are close to the hidden outcrop line of the coal seam, the classification characteristic value of the threat degree is greater than 3.5, which is in the high-threat zone for disasters caused by roof thermal storage aquifers during coal seam mining. The area above the medium-threat zone accounts for 71.82% of the total study area, indicating that deep coal mining is affected by multiple factors and that roof water and heat disasters are more likely to occur.